Evaluation and mitigation of modelling errors in numerical simulations of mooring line and seabed contact - Low, Chee Meng (2019)
Time-domain mooring simulation is a direct and effective method of evaluating mooring line loads and floater motions, in which nonlinear effects including drag forces and seabed interaction are readily accounted for. The formulation of seabed models affects the accuracy of line loads, including maximum tension as well as fatigue results, and also floater motions in coupled simulations. The interaction between the seabed and discrete line structural models is challenging in time-domain numerical simulations and a myriad of seabed models have been proposed in the literature. However, issues such as the selection of suitable seabed force coefficients and the application of suitable line discretisations, to achieve a balance between accuracy and computational cost, remain challenging problems to be resolved. This thesis investigates the shortcomings of existing numerical methods in accurately capturing the dynamic mooring line-seabed interaction and proposes new solutions.